2019
DOI: 10.1002/rmv.2025
|View full text |Cite
|
Sign up to set email alerts
|

Expressional activation and functional roles of human endogenous retroviruses in cancers

Abstract: Summary Human endogenous retroviruses (HERVs) are widely believed to be remnants of ancestral germ line infections by exogenous retroviruses. Although HERVs are deemed as “nonfunctional DNAs” due to loss of most of their viral protein coding capacity during evolution as part of the human genome, cumulative evidences are showing the expressional activation and potential roles of HERVs in diseases especially cancers. Work by other researchers and us has observed the dysregulation of HERVs in cancers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 142 publications
(274 reference statements)
1
61
0
2
Order By: Relevance
“…Despite this not being the objective of the present study, the association between HERV-K and breast cancer in humans was confirmed. HERV-K in human breast cancer are involved in the processes of replication and tumorigenesis [88], derived directly from the protein and gene activities of mobile elements in the host [12]. This association is supported by the literature, indicating that this disease could be caused by the presence of HERVs in chromosomes 6, 7, 8, and 19 [26].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Despite this not being the objective of the present study, the association between HERV-K and breast cancer in humans was confirmed. HERV-K in human breast cancer are involved in the processes of replication and tumorigenesis [88], derived directly from the protein and gene activities of mobile elements in the host [12]. This association is supported by the literature, indicating that this disease could be caused by the presence of HERVs in chromosomes 6, 7, 8, and 19 [26].…”
Section: Discussionsupporting
confidence: 53%
“…In humans, these elements (or TE-derived sequences) comprise~50-70% of the sequenced genome [8]. Several studies have indicated that TEs play crucial genomic roles involved in chromosome structuring, structural variation, the alteration of gene expression [5,7], evolution, the variation of genomic size, and environmental adaptation [9][10][11][12][13]. Nevertheless, these elements can also be associated with human diseases, such as different types of cancer [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HERV families are originally named by adding the one-letter code of the amino acid specificity of the most likely tRNA as a suffix to the acronym HERV (4). HERV sequences are composed of four protein-encoding genes (gag, pro, pol, and env) flanked at the 5 ′ and 3 ′ ends by two regulatory regions named long terminal repeats (LTRs) (5). In the course of evolution, those sequences accumulated several mutations that eventually led to gene silencing (1).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of evolution, those sequences accumulated several mutations that eventually led to gene silencing (1). Under normal conditions, HERV gene expression is highly regulated by multiple mechanisms, such as acetylation and methylation (5). However, abnormal HERV gene and protein expression has been documented in cases of malignancy (6), neuroinflammation (7), and autoimmune diseases (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation